2012
DOI: 10.1073/pnas.1205063109
|View full text |Cite
|
Sign up to set email alerts
|

Nascent RNA structure modulates the transcriptional dynamics of RNA polymerases

Abstract: RNA polymerase pausing represents an important mechanism of transcriptional regulation. In this study, we use a single-molecule transcription assay to investigate the effect of template base-pair composition on pausing by RNA polymerase II and the evolutionarily distinct mitochondrial polymerase Rpo41. For both enzymes, pauses are shorter and less frequent on GC-rich templates. Significantly, incubation with RNase abolishes the template dependence of pausing. A kinetic model, wherein the secondary structure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
130
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(141 citation statements)
references
References 48 publications
11
130
0
Order By: Relevance
“…It was proposed that the secondary structure of the transcribed RNA presents an energetic barrier for polymerase backtracking, thus preventing the polymerase to go into a deep backtrack and reducing the overall backtracking time (67). Theoretical predictions were confirmed experimentally in an optical tweezers study that showed that the GC content of the DNA template and hence, the nascent RNA structure, affects the pausing dynamics of RNA polymerases, with polymerases pausing less on the GC-rich templates that are known to form more secondary structures (34). The energy barrier to backtracking due to the secondary structure of the RNA is also considered in a recent theoretical study, where the entropy produced during backtracking is discussed (68).…”
Section: Pausing Of Rna Polymerasessupporting
confidence: 54%
See 1 more Smart Citation
“…It was proposed that the secondary structure of the transcribed RNA presents an energetic barrier for polymerase backtracking, thus preventing the polymerase to go into a deep backtrack and reducing the overall backtracking time (67). Theoretical predictions were confirmed experimentally in an optical tweezers study that showed that the GC content of the DNA template and hence, the nascent RNA structure, affects the pausing dynamics of RNA polymerases, with polymerases pausing less on the GC-rich templates that are known to form more secondary structures (34). The energy barrier to backtracking due to the secondary structure of the RNA is also considered in a recent theoretical study, where the entropy produced during backtracking is discussed (68).…”
Section: Pausing Of Rna Polymerasessupporting
confidence: 54%
“…Depending on the experimental system, i.e. assisting or opposing force mode and the concentration of nucleotides used, the measured velocity ranged between 15 and 25 nt/s (9,11,21,22,(33)(34)(35).…”
Section: Elongation Dynamics Of Rna Polymerasesmentioning
confidence: 99%
“…The rate of RNAP II backtracking in the absence of RNA 3′ end retraction is about one nucleotide per 0.3 s, about 20-fold slower than forward polymerization. 96 Assuming a similar rate for RNAP III, for the ~20% of tRNA genes that have a predicted structure 4-5 nts upstream of the T tract, the required backtracking would represent a relatively slow step. For the dozens of genes with hairpins farther upstream, 6-12 nts, 13 the required backtracking would be more time consuming.…”
mentioning
confidence: 99%
“…27 It was hypothesized that secondary structure in the nascent RNA would prevent RNAP II backtracking by presenting an energy barrier to backward movement of the polymerase. RNAP II pause duration and density was compared on GC-rich vs. AT-rich templates; transcripts made from the GC-rich templates would form stronger hairpins.…”
Section: Optical Tweezers Studies Reveal New Aspects Of the Mechanismmentioning
confidence: 99%